Investigating the role the PI3K pathway plays in ependymoma pathogenesis - Estranero, Jasper (2019)
Introduction: Ependymoma is the second most common malignancy of the central nervous system in paediatric cohorts, accounting for 6-12% of all cases of childhood brain tumours. Its clinical management remains a challenge at present, generally manifesting poor patient prognoses with a paucity of effective treatments. It was previously found that the PI3K signalling pathway, a cell survival cascade implicated in many cancers, was activated in 72% of primary ependymomas which suggests a significant role in disease pathogenesis. The PI3K pathway regulates a range of cellular processes that support tumourigenesis and its targeting has yielded therapeutic benefits in many malignancies. This study investigated the impact of signalling through the PI3K pathway in ependymoma survival and its prospect as an alternative target to treat these tumours.